2022
DOI: 10.1186/s12889-022-12795-9
|View full text |Cite
|
Sign up to set email alerts
|

Invasive meningococcal disease in older adults in North America and Europe: is this the time for action? A review of the literature

Abstract: Background Neisseria meningitidis is an encapsulated Gram-negative diplococcus that asymptomatically colonises the upper respiratory tract in up to 25% of the population (mainly adolescents and young adults). Invasive meningococcal disease (IMD) caused by Neisseria meningitidis imposes a substantial public health burden,. The case fatality rate (CFR) of IMD remains high. IMD epidemiology varies markedly by region and over time, and there appears to be a shift in the epidemiology towards older a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 101 publications
(139 reference statements)
3
23
0
Order By: Relevance
“… 74 , 75 Atypical symptoms of IMD have been reported in older adults, which makes diagnoses difficult, allowing the disease to progress without treatment. 76 The financial burden of hospitalization and treatment of IMD-related sequelae on the individual and society is substantial. 71 , 74 Vaccinating older adults ≥50 years of age irrespective of the risk factors can reduce the healthcare burden and mortality in this age group.…”
Section: Discussionmentioning
confidence: 99%
“… 74 , 75 Atypical symptoms of IMD have been reported in older adults, which makes diagnoses difficult, allowing the disease to progress without treatment. 76 The financial burden of hospitalization and treatment of IMD-related sequelae on the individual and society is substantial. 71 , 74 Vaccinating older adults ≥50 years of age irrespective of the risk factors can reduce the healthcare burden and mortality in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns have been observed in other settings with established infant or adolescent meningococcal immunization programs, where declines in vaccine eligible age-groups have led to a greater relative burden in adults. 7 , 13 , 14 Compulsory Hajj/Umrah pilgrim MenACWY immunization in individuals within these GCC Countries could also have had some impact.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the greatest burden and highest incidence of IMD is in infants and young children, with a second peak in adolescents, 1 , 4 , 5 while more recent epidemiological trends indicate an increased burden in adults and the elderly, where case fatality rates (CFRs) are also higher. 1 , 7 , 13 , 14 Global epidemiology shows substantial geographical variation, both in terms of disease burden and in the relative importance of specific serogroups in local or regional IMD epidemiology, 1 , 4 , 5 with temporal shifts driven by both cyclic epidemiologic patterns, disease outbreaks, 15 and the introduction of effective vaccines against major pathogenic serogroups. Use of conjugated monovalent MenC vaccines, quadrivalent MenACWY vaccines and protein-based vaccines against MenB in national immunization programs (NIPs), mostly targeting infants and adolescents, has led to substantial declines in the IMD burden in these at-risk populations, 1 , 5 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis study indicated that, for laboratory-confirmed IMD cases reported between January 2000 and May 2008, the predicted CFR was high in infants (9.0%), gradually decreased to 7.0% in 7 year olds, subsequently increased to reach a peak of 15.0% in young adults, remained steady in adults aged between 28 and 45 years, and then rose rapidly in older adults ( 1 ). Older adults usually have the highest mortality rate of IMD, which could be linked to underlying comorbidities and more atypical presentations hindering appropriate timely diagnosis and management and the dysfunction of the immune response ( 14 , 40 ). However, little has been discussed on the elevated CFRs in the young adult group.…”
Section: Discussionmentioning
confidence: 99%